THE EFFECT OF 4P MARKETING MIX ON SATISFACTION J&T EXPRESS SAENTIS SERVICE USERS, MEDAN BRANCH - Afandi, Bima; Parhusip , Austin Alexander (Sean Institute, 2023)
Marketing Mix is ​​one of the main concepts in modern marketing, which has an important role in influencing customers to buy products and services offered by the market, therefore the marketing mix is ​​said to be a tool that will show the level of marketing success. To find out whether there is an effect of product, price, place, and promotion on the satisfaction of users of the J&T Express Saentis Delivery Service Medan branch. This type of research uses quantitative research methods with primary and secondary data sources. The number of samples in this study was 100 respondents who were determined using the Wibisono formula and purposive sampling technique, namely the technique of determining the sample based on certain considerations. This study uses SPSS 20.0 as a data processing tool. The results of this study indicate that the product has a positive and significant effect on J&T Express customer satisfaction, Price has a positive and significant effect on J&T Express customer satisfaction Place has a positive and significant effect on JN&Express customer satisfaction, and Promotion has a positive and significant effect on customer satisfaction. J&T Express customers. Meanwhile, Product, Price, Place, and Promotion simultaneously have a positive and significant effect on J&T Express customer satisfaction.